(untitled) (Semiárida, 2026)
The Reconquista River Basin, located in the province of Buenos Aires, is under significant environmental pressure due to the concentration of industrial, urban, and vehicular activities. To obtain reliable information on air quality in the region, the Ministry of Environment and the Reconquista River Basin Committee (COMIREC) launched the Air Quality Monitoring and Enforcement Project (PROMFCA) in December 2023. The project carried out monitoring campaigns at ten strategically selected sites across the basin, focusing on the measurement of particulate matter (PM2.5 and PM10). Air Quality Index (AQI) values were also calculated using the US-EPA methodology, allowing for the classification of pollution levels and their impact on health. The results were integrated into a publicly accessible web-based cartographic platform, which enables spatial analysis and visualization of air quality. This initiative demonstrates the feasibility of applying international standards at the local level and lays the groundwork for evidence-based environmental management.